The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1097/ju.0000000000001422
|View full text |Cite
|
Sign up to set email alerts
|

T1 Substaging of Nonmuscle Invasive Bladder Cancer is Associated with bacillus Calmette-Guérin Failure and Improves Patient Stratification at Diagnosis

Abstract: Purpose: Currently, markers are lacking that can identify patients with high risk nonmuscle invasive bladder cancer who will fail bacillus Calmette-Gu erin treatment. Therefore, we evaluated the prognostic value of T1 substaging in patients with primary high risk nonmuscle invasive bladder cancer. Materials and Methods: Patients with primary high risk nonmuscle invasive bladder cancer who received !5 bacillus Calmette-Gu erin induction instillations were included. All tumors were centrally reviewed, which incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 25 publications
3
39
0
Order By: Relevance
“…Finally, in our study, the BCG showed a significant impact on prolonging PFS only for T1 a patients. This outcome is in line with the retrospective study of de Jong FC ( 27 ); the authors identified 264 patients with high-grade pT1 tumors and subdivided them as having extensive lamina propria invasion (73%) or microinvasion (27%) according to the substaging T1 m− e . With a median follow-up of 68 months, patients with T1 e had a statistically significant difference in BCG failure (41 vs. 51%; P = 0.002).…”
Section: Discussionsupporting
confidence: 81%
“…Finally, in our study, the BCG showed a significant impact on prolonging PFS only for T1 a patients. This outcome is in line with the retrospective study of de Jong FC ( 27 ); the authors identified 264 patients with high-grade pT1 tumors and subdivided them as having extensive lamina propria invasion (73%) or microinvasion (27%) according to the substaging T1 m− e . With a median follow-up of 68 months, patients with T1 e had a statistically significant difference in BCG failure (41 vs. 51%; P = 0.002).…”
Section: Discussionsupporting
confidence: 81%
“…Formalin fixed paraffin-embedded (FFPE) material, including TURBTs, re-TURBTs, tumor recurrences, random biopsies, radical cystectomies (RC), pelvic lymph node dissections (PLND) and distant metastases were reviewed by an expert uropathologist (R.F.H.) in accordance with WHO standards for classification of the urinary system and was previously published [3, 80]. Patients were classified as high risk or as very high risk subgroup according to the EAU guidelines on NMIBC.…”
Section: Methodsmentioning
confidence: 99%
“…Initial treatment response to BCG is excellent, yet the long-term efficacy is moderate as HR-NMIBC patients have a 50% risk of developing recurrent disease within 5 years [2]. Furthermore, a 20% risk of progression to advanced disease is observed, which is associated with high mortality [1, 3]. Patients with HR-NMIBC where a tumor recurs or progresses have been exposed to unnecessary BCG toxicity, a delay in radical treatment and have reduced survival [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of BCR in the FT group is concerning and will require more analysis with larger patient groups. 6 Patients were stratified into groups of T1m (microscopic) and T1e (extensive) invasion of the lamina propria. Of those with T1e 41% failed BCG treatment with a high grade recurrence compared to 21% with T1m.…”
Section: Primary Prostate Cancer Therapy and Salvage Prostatectomy Toxicitymentioning
confidence: 99%